Risk of newly diagnosed interstitial lung disease after COVID-19 and impact of vaccination: a nationwide population-based cohort study - Kim, Bo-Guen; Lee, Hyun; Jeong, Cho Yun; Yeom, Sang Woo; Park, Dong Won; Park, Tai Sun; Moon, Ji-Yong; Kim, Tae-Hyung; Sohn, Jang Won; Yoon, Ho Joo; Kim, Jong Seung; Kim, Sang-Heon (Frontiers in Public Health, 2024)
Objectives: Previous studies suggested that coronavirus disease 2019 (COVID-19) could lead to pulmonary fibrosis, but the incidence of newly diagnosed interstitial lung disease (ILD) after COVID-19 is unclear. We aimed to determine whether COVID-19 increases the risk of newly diagnosed ILD and whether vaccination against COVID-19 can reduce this risk.: This retrospective cohort study used data from the Korean National Health Insurance claim-based database. Two study groups and propensity score-matched control groups were constructed: Study 1: participants diagnosed with COVID-19 and their PS-matched controls; Study 2: COVID-19 vaccinated participants and their PS-matched controls.In study 1, during a median 6 months of follow-up, 0.50% of the COVID-19 cohort (300/60,518) and 0.04% of controls (27/60,518) developed newly diagnosed ILD, with an incidence of 9.76 and 0.88 per 1,000 person-years, respectively. Participants diagnosed with COVID-19 had a higher risk of ILD (adjusted hazard ratio [aHR], 11.01; 95% confidence interval [CI], 7.42-16.32) than subjects without COVID-19. In study 2, participants in the vaccination cohort had a lower risk of newly diagnosed ILD than their PS-matched controls (aHR, 0.44; 95% CI, 0.34-0.57).Using nationwide data, we demonstrated that COVID-19 was associated with a higher incidence rate of newly diagnosed ILD, but that this risk could be mitigated by COVID-19 vaccination.